Infantile esotropia: emergence of binocular function years after surgery - Reich-d'Almeida, Isabel (2017)
Purpose - To demonstrate that in surgically treated infantile esotropia patients, it is possible, after a very long therapy and follow-up period, to achieve functional rehabilitation well above the conventionally accepted age for sensorial recovery.